Association studies of the copy-number variable ß-defensin cluster on 8p23.1 in adenocarcinoma and chronic pancreatitis - Taudien Stefan; Gäbel Gabor; Kuss Oliver; Groth Marco; Grützmann Robert; Huse Klaus; Kluttig Alexander; Wolf Andreas; Nothnagel Michael; Rosenstiel Philip; Greiser Karin Halina; Werdan Karl; et al. (BMC Research Notes, 2012)
Abstract Background Human ß-defensins are a family of antimicrobial peptides located at the mucosal surface. Both sequence multi-site variations (MSV) and copy-number variants (CNV) of the defensin-encoding genes are associated with increased risk for various diseases, including cancer and inflammatory conditions such as psoriasis and acute pancreatitis. In a case–control study, we investigated the association between MSV in DEFB104 as well as defensin gene (DEF) cluster copy number (CN), and pancreatic ductal adenocarcinoma (PDAC) and chronic pancreatitis (CP). Results Two groups of PDAC (N=70) and CP (N=60) patients were compared to matched healthy control groups CARLA1 (N=232) and CARLA2 (N=160), respectively. Four DEFB104 MSV were haplotyped by PCR, cloning and sequencing. DEF cluster CN was determined by multiplex ligation-dependent probe amplification. Neither the PDAC nor the CP cohorts show significant differences in the DEFB104 haplotype distribution compared to the respective control groups CARLA1 and CARLA2, respectively. The diploid DEF cluster CN exhibit a significantly different distribution between PDAC and CARLA1 (Fisher’s exact test P=0.027), but not between CP and CARLA2 (P=0.867). Conclusion Different DEF cluster b CN distribution between PDAC patients and healthy controls indicate a potential protective effect of higher CNs against the disease.